Building empire, creating markets: commercial policies and practices in imperial Qin (221-207 BCE) - Korolkov, Maxim (Journal of the economic and social history of the Orient, 2023)
The expansion of states played a crucial role in the commercial growth in the ancient world. The empires provided physical infrastructures, such as roads, and institutions, such as legal order and standardized currencies, that reduced the transaction costs of economic exchanges. Expensive activities by the imperial governments, including military conquests and urban development, required efficient mechanisms for accumulating, transforming, and transferring resources, and markets often provided such mechanisms. This article explores the relationship between empire-building and commercial change in the Qin Empire (221-207 BCE), the first of China’s centralized empires. I demonstrate how the empire’s need to administer and tax its territories contributed to the growth of markets.
Gesehen am 13.12.2023